Cultural Pearls from the East: In Memory of Shmuel Moreh (1932-2017) - Scheffer, Yona; Hatina, Meir (Studies on Performing Arts & Literature of the Islamicate World, 2021)
Cultural Pearls from the East offers fascinating insights into Muslim-Arab culture and the evolution of its intellectual nature and literary texts from early Islam to modern times. The textual analysis of largely unexplored literary works and chronicles that epitomize this volume highlight the affinity between culture, society, and politics, exploring these issues from both thematic and comparative perspectives. Among the topics examined in depth: Arabic poetry of warfare at the dawn of Islam; medieval poems about venerated sites and saints; Ottoman and Egyptian chronicles portraying the socioreligious landscapes of Egypt and the Fertile Crescent under the Ottoman Empire and in the shadow of growing European encroachment; and Arab-Jewish literature dealing with suppression, exile, and identity. Contributors: Ghaleb Anabseh, Albert Arazi, Meir M. Bar-Asher, Peter Chelkowski, Geula Elimelekh, Sigal Goorj, Jane Hathaway, Meir Hatina, Yair Huri-Horesh, Amir Lerner, Menachem Milson, Gabriel M. Rosenbaum, Joseph Sadan, Yona Sheffer, Norman (Noam) A. Stillman, Ibrahim Taha, Michael Winter, Eman Younis.